Cactus Pear (Opuntia ficus-indica): A Versatile and Sustainable Crop for Food, Fuel, Fodder, and Fertilizer - Hassan, Sawsan; Louhaichi, Mounir (Krishi Publisher, 2023)
The review was presented at the International Conference On Feeding the Future through Sustainable Eco-friendly Innovations in Rangeland, Forages, and Animal Sciences in Bangalore, India. This presentation explored the potential of Cactus pear (Opuntia ficus-indica) as a versatile and sustainable crop in arid and semi-arid regions. It highlighted its role in food production, biofuel generation, livestock feed, and soil improvement. The review emphasized cactus pear's adaptability to regions with limited water resources and its nutritional value. Challenges such as labor-intensive harvesting and post-harvest losses were noted, along with its potential for biofuel production and biofertilizer use. The abstract concluded that collaborative research was crucial to fully realize cactus pear's potential for sustainable agriculture in arid regions.